1993
DOI: 10.1007/bf01740904
|View full text |Cite
|
Sign up to set email alerts
|

Cure of mice bearing a late-stage, highly metastatic, drug-resistant tumor by adoptive chemoimmunotherapy

Abstract: We show here that in contrast to BALB/c mice bearing a late-stage, large MOPC-315 plasmacytoma, BALB/c mice bearing a late-stage, large RPC-5 plasmacytoma were not cured by cyclophosphamide therapy (15, 50, 100 or 200 mg/kg). However, most BALB/c mice bearing a late-stage RPC-5 tumor were cured by cyclophosphamide therapy (100 mg/kg) in conjunction with adoptive immunotherapy using tumor-infiltrated spleen cells (TISpC) that had been cultured with inactivated RPC-5 tumor cells plus polyethylene glycol 6000, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In conclusion, our data strongly suggest that CTX induces release of soluble factors that can enhance the proliferation, differentiation, and activity of tumor-specific immune T cells. These results could lead to a general reinterpretation of the synergistic effects of CTX and immunotherapy observed by others in experimental models (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), generally assumed to be mediated by effects on suppressor T cells. The data reported in this article may have more general implications on the relationships between the homeostatic mechanisms generated as a consequence of events perturbing the lymphohemopoietic equilibrium and the survival, expansion, and differentiation of immune cells endowed with a given T cell repertoire.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In conclusion, our data strongly suggest that CTX induces release of soluble factors that can enhance the proliferation, differentiation, and activity of tumor-specific immune T cells. These results could lead to a general reinterpretation of the synergistic effects of CTX and immunotherapy observed by others in experimental models (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), generally assumed to be mediated by effects on suppressor T cells. The data reported in this article may have more general implications on the relationships between the homeostatic mechanisms generated as a consequence of events perturbing the lymphohemopoietic equilibrium and the survival, expansion, and differentiation of immune cells endowed with a given T cell repertoire.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, an ensemble of experiments indicated that an intact immune system of the recipient host and some soluble factors (IFN-␣ / ␤ ) were essential in mediating the antitumor response to the adoptive immunotherapy in the CTX-injected animals. Altogether, these results may lead to reinterpretation of the mechanisms underlying the synergistic effects of CTX and adoptive immunotherapy observed in various experimental tumor models by others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), largely explained on the assumption of a selective effect of CTX on "suppressor T cells" (24,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…We did not specifically aim to optimize the treatment schedule in the present study. Nevertheless, increased efficacy of liposomal muramyl peptides is likely to result from combination with, for instance, chemotherapy [29][30][31]. Also, efficacy may be improved when using an alternating treatment schedule with immunomodulators triggering different macrophage activating pathways, thus preventing the effector cells becoming refractory to subsequent stimulation [32].…”
Section: Discussionmentioning
confidence: 99%